Individualised Estimation of Quality-adjusted Survival Benefit and Cost-effectiveness of Proton Beam Therapy in Intermediate-stage Hodgkin Lymphoma. Issue 5 (May 2023) - Jones, D.A.; Candio, P.; Shakir, R.; Ramroth, J.; Wolstenholme, J.; Gray, A.M.; Cutter, D.J.; Ntentas, G.
Abstract: Aims: Radiotherapy for Hodgkin lymphoma leads to the irradiation of organs at risk (OAR), which may confer excess risks of late effects. Comparative dosimetry studies show that proton beam therapy (PBT) may reduce OAR irradiation compared with photon radiotherapy, but PBT is more expensive and treatment capacity is limited. The purpose of this study is to inform the appropriateness of PBT for intermediate-stage Hodgkin lymphoma (ISHL). Materials and methods: A microsimulation model simulating the course of ISHL, background mortality and late effects was used to estimate comparative quality-adjusted life years (QALYs) lived and healthcare costs after consolidative pencil beam scanning PBT or volumetric modulated arc therapy (VMAT), both in deep-inspiration breath-hold. Outcomes were compared for 606 illustrative patients covering a spectrum of clinical presentations, varying by two age strata (20 and 40 years), both sexes, three smoking statuses (never, former and current) and 61 pairs of OAR radiation doses from a comparative planning study. Both undiscounted and discounted outcomes at 3.5% yearly discount were estimated. The maximum excess cost of PBT that might be considered cost-effective by the UK's National Institute for Health and Care Excellence was calculated. Results: OAR doses, smoking status and discount rate had large impacts on QALYs gained with PBT. Current smokers benefited the most, averaging 0.605 undiscounted QALYs (range –0.341 to 2.171) and 0.146 discounted QALYs (range –0.067 to 0.686), whereas never smokers benefited the least, averaging 0.074 undiscounted QALYs (range –0.196 to 0.491) and 0.017 discounted QALYs (range –0.030 to 0.086). For the gain in discounted QALYs to be considered cost-effective, PBT would have to cost at most £4812 more than VMAT for current smokers and £645 more for never smokers. This is below preliminary National Health Service cost estimates of PBT over photon radiotherapy. Conclusion: In a UK setting, PBT for ISHL may not be considered cost-effective. However, the degree of unquantifiable uncertainty is substantial. Highlights: Proton beam therapy offers dosimetric advantage over photon radiotherapy. Lifetime modelling needed to estimate comparative benefits and cost-effectiveness. Baseline risks such as smoking increased quality adjusted survival benefit. Proton beam therapy unlikely to be cost-effective in UK under NICE threshold. There is a large amount of unquantifiable uncertainty when using modelling approach.